2015
DOI: 10.1016/j.nbd.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing anti-interleukin-1β antibodies modulate fetal blood–brain barrier function after ischemia

Abstract: We have previously shown that increases in blood-brain barrier permeability represent an important component of ischemia-reperfusion related brain injury in the fetus. Pro-inflammatory cytokines could contribute to these abnormalities in blood-brain barrier function. We have generated pharmacological quantities of mouse anti-ovine interleukin-1β monoclonal antibody and shown that this antibody has very high sensitivity and specificity for interleukin-1β protein. This antibody also neutralizes the effects of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 53 publications
(97 reference statements)
6
79
0
Order By: Relevance
“…Consistent with our previous findings, brain ischemia and reperfusion did not have a major impact on the systemic hemodynamic and biochemical homeostasis in the fetus. 12,19 The findings of our study show that systemically administered IL-1β is able to cross the BBB in significant amounts to reach the brain during normal homeostatic conditions in the fetus. This finding suggests that conditions such as perinatal inflammation that result in increases in systemic pro-inflammatory cytokines could facilitate cytokines to cross the intact BBB and cause brain injury before birth even under nonischemic conditions.…”
Section: Mabp (Mm Hg)mentioning
confidence: 72%
See 3 more Smart Citations
“…Consistent with our previous findings, brain ischemia and reperfusion did not have a major impact on the systemic hemodynamic and biochemical homeostasis in the fetus. 12,19 The findings of our study show that systemically administered IL-1β is able to cross the BBB in significant amounts to reach the brain during normal homeostatic conditions in the fetus. This finding suggests that conditions such as perinatal inflammation that result in increases in systemic pro-inflammatory cytokines could facilitate cytokines to cross the intact BBB and cause brain injury before birth even under nonischemic conditions.…”
Section: Mabp (Mm Hg)mentioning
confidence: 72%
“…[20][21][22] In addition, we have recently shown that BBB dysfunction represents an important component of ischemicreperfusion related brain injury in the fetus, 12 and that the proinflammatory cytokine IL-1β contributes to this barrier dysfunction. 19 Nonetheless, although it has been suggested that systemic cytokines might gain access to the fetal brain by crossing the BBB, 4 there is a paucity of direct experimental evidence to support this concept and no quantitative data measuring BBB permeability with cytokines in the fetal or neonatal brain. Therefore, the objectives of the current study were to determine the ability of systemic circulating IL-1β to cross the intact BBB under homeostatic conditions in the normal fetus, and to determine whether ischemia accentuates the transfer of IL-1β across the BBB in the fetus.…”
Section: Mabp (Mm Hg)mentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the isotope alpha-[ 14 C]-aminioisobutyric acid is a tracer introduced into the circulation along with a red blood cell labeling agent, technetium-99 m . The amount of tracer that has moved out of the vasculature across the BBB can be described by a transfer constant, Ki by differentiating the parenchymal tracer concentration from the intravascular tracer, using co-localization with red blood cells labeled with technetium-99 m [32,33].…”
Section: Preclinical Measurements Of Bbb Permeabilitymentioning
confidence: 99%